2017
DOI: 10.1002/2017jd026831
|View full text |Cite
|
Sign up to set email alerts
|

A case study of convectively sourced water vapor observed in the overworld stratosphere over the United States

Abstract: On 27 August 2013, during the Studies of Emissions and Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys field mission, NASA's ER‐2 research aircraft encountered a region of enhanced water vapor, extending over a depth of approximately 2 km and a minimum areal extent of 20,000 km2 in the stratosphere (375 K to 415 K potential temperature), south of the Great Lakes (42°N, 90°W). Water vapor mixing ratios in this plume, measured by the Harvard Water Vapor instrument, constitute the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
128
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(143 citation statements)
references
References 117 publications
(191 reference statements)
13
128
2
Order By: Relevance
“…These dates are 8, 16 and 27 August 2013. Similar results are seen from other hygrometers on the NASA ER-2 aircraft (Smith et al, 2015). For each of these ER-2 flights, the back trajectories are presented along with the intersection of coincident OT.…”
Section: Case Studiessupporting
confidence: 64%
See 1 more Smart Citation
“…These dates are 8, 16 and 27 August 2013. Similar results are seen from other hygrometers on the NASA ER-2 aircraft (Smith et al, 2015). For each of these ER-2 flights, the back trajectories are presented along with the intersection of coincident OT.…”
Section: Case Studiessupporting
confidence: 64%
“…Enhanced water vapor measured in situ by both the JLH Mark2 instrument ( Fig. 1) and the Harvard Water Vapor instrument (Smith et al, 2015) on the NASA ER-2 aircraft indicated that the aircraft intercepted convectively influenced air. Other tracers measured on the aircraft did not change significantly in these plumes.…”
Section: Aircraftmentioning
confidence: 99%
“…Observations of meteorological conditions in the midlatitudes have indicated the potential for chlorine activation and halogen‐catalyzed ozone loss in the lower stratosphere during the summer. Water vapor enhancements resulting from transport by tropopause‐penetrating convection, a consistent product of the unique climate of the summertime Central United States (Anderson et al, ; Anderson et al, ; Dessler & Sherwood, ; Hanisco et al, ; Ray et al, ; Schwartz et al, ; Smith et al, ; Sun & Huang, ; Toon et al, ; E. M. Weinstock et al, ), can move the conditions of the lower stratosphere into a state favorable to halogen activation and ozone loss particularly when low temperatures are present. The sensitivity of the lower stratosphere to convective water vapor enhancements is a direct result of the chlorine activation heterogeneous chemistry that is favored by high humidity, low temperatures, and larger sulfate aerosol surface area density (SAD; Anderson et al, ; Anderson et al, ; Anderson & Clapp, ; Carslaw et al, ; Drdla & Müller, ; Hanson, ; Horn et al, ; Murphy & Ravishankara, ; Portmann et al, ; Shi et al, ; S. Solomon et al, ; S. Solomon, ; Tabazadeh et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Observations of water vapor enhancements in coherent plumes have also been made up to between 7 and 12 days after convective injection (Pittman et al, ; Ray et al, ; Weinstock et al, ). Observations of a convectively sourced stratospheric water vapor plume show a minimum special extent of 20,000 km 2 between the pressure levels of 70 and 115 hPa and estimate a potentially more realistic area of up to 100,000 km 2 at 115 hPa given the exponential altitude dependence of convective volumes in the lower stratosphere (Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation